Determination of Nitroaromatics Using a Double-Layer of Gelatin Nanofibers and a Pyrene-Doped Polystyrene Membrane. (12th December 2018) - Wang, Jiemei; Yu, Runhui; Tao, Furong; Cui, Yuezhi; Li, Tianduo
ABSTRACT: A double-layered sensor was prepared by an electrospinning method using pyrene, polystyrene, and gelatine to prepare a pyrene-polystyrene/gelatin/glass device for the determination of nitroaromatics. The pyrene- polystyrene top layer, which was an electronspun membrane from a mixture of the starting materials in 3:1 N, N-dimethylformaide:tetrahydrofuan, served as the sensing layer for detecting 2, 4-dinitrotoluene. The bottom layer was the gelatin electrospun membrane that served as an intermediate between the top layer and the glass slide. The dinitrotoluene analyte was transferred into the sensing layer above and below due to the porosity of the gelatin layer. With a large number of hydroxyl and amino groups, the gelatin layer formed hydrogen bonds with the 2, 4-dinitrotoluene molecules, which caused the enrichment of the analyte around the gelatin layer. Additionally, single-layer pyrene-polystyrene/glass sensor was also prepared for control measurements. The quenching efficiency of the pyrene-polystyrene/gelatin/glass sensor was 76.7% at equilibrium obtained within 6 minutes, while the monolayer sensor pyrene–polystyrene/glass device provided 65.8% quenching efficiency within 6 minutes. The gelatin layer played an important role in the superior performance of the double-layered sensor.